2017
DOI: 10.1055/s-0036-1597823
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of CAD/CAM-Assisted versus Conventional Microvascular, Fibular Free Flap Reconstruction of the Mandible: A Retrospective Study of 30 Cases

Abstract: Different advantages of virtually planned and guided mandibular reconstructions have been described. Functional analyses and comparisons with conventionally reconstructed patients. We retrospectively analyzed 30 cases of mandibular reconstructions that involved virtually planned or conventional microvascular, fibular free flaps that occurred between April 2011 and December 2014 at a single center. The results were also compared with a healthy cohort of 30 participants. Axiographic measurements were performed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…In mandibular reconstruction using an FF after segmental mandibular resection, a guide constructed using CAD/CAM enabled more accurate reconstruction. 7 Such prostheses had an average postoperative deviation of the condyle from the preoperative position of 3.8 mm (range 1.3–6.7). 8 However, for reconstructions not including the condyle using a CAD/CAM guide, the postoperative deviations from the virtual plan were 2.4 mm 9 and 2.7 mm.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In mandibular reconstruction using an FF after segmental mandibular resection, a guide constructed using CAD/CAM enabled more accurate reconstruction. 7 Such prostheses had an average postoperative deviation of the condyle from the preoperative position of 3.8 mm (range 1.3–6.7). 8 However, for reconstructions not including the condyle using a CAD/CAM guide, the postoperative deviations from the virtual plan were 2.4 mm 9 and 2.7 mm.…”
Section: Discussionmentioning
confidence: 98%
“…The advantage of using a CAD/CAM guide for the latter operation has been reported. 7 , 9 In such mandibular reconstructions, even if surgeons do not use the CAD/CAM guide, they can image the reproduction position easily by intermaxillary fixation because both ends of the mandible are retained. However, when reconstructing the mandible after hemimandibulectomy including the condyle, it is more difficult to image the final position even when setting intermaxillary fixation because there are few landmarks, and there is only the healthy side of the mandible remaining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the introduction of virtually-designed surgical guides, this complexity decreases, as these guidelines allow the surgeon to plan the reconstruction with greater precision to maximize the final result ( 4 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed to a greater accuracy in the design of fibular graft osteotomies with the use of computer-aided surgical guides ( 3 , 4 , 12 - 19 ). In a control case study of 38 patients treated by mandibular reconstructions with fibula grafts, Hanasono et al ( 14 ) concluded that CAD/CAM and stereolithographic models increased their accuracy and speed.…”
Section: Discussionmentioning
confidence: 99%